2011
DOI: 10.1111/j.1745-9125.2011.00225.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Ethnic Threat and Social Control: Examining Public Support for Judicial Use of Ethnicity in Punishment*

Abstract: Research on social inequality in punishment has focused for a long time on the complex relationship among race, ethnicity, and criminal sentencing, with a particular interest in the theoretical importance that group threat plays in the exercise of social control in society. Prior research typically relies on aggregate measures of group threat and focuses on racial rather than on ethnic group composition. The current study uses data from a nationally representative sample of U.S. residents to investigate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 98 publications
5
48
1
1
Order By: Relevance
“…In addition to the lines of research discussed above, the role of perceptions about the ethnic makeup of delinquents in shaping public views about juvenile justice is a theme that bears greater attention. Two recent studies have shown that stereotypes associating Latinos with crime influence views about criminal punishments (Johnson et al, 2011; Welch et al, 2011). However, no research has examined whether the ethnic typification of delinquency is related to punitiveness toward juvenile offenders.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the lines of research discussed above, the role of perceptions about the ethnic makeup of delinquents in shaping public views about juvenile justice is a theme that bears greater attention. Two recent studies have shown that stereotypes associating Latinos with crime influence views about criminal punishments (Johnson et al, 2011; Welch et al, 2011). However, no research has examined whether the ethnic typification of delinquency is related to punitiveness toward juvenile offenders.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars have long drawn general links between perceived social threats and the use of formal social control efforts, including the reporting of crimes to the police (Blalock, 1967;King & Wheelock, 2007;Stults & Baumer, 2007;Warner, 1992). In drawing on these ideas, scholars have recently suggested that punitive sentiment and the mobilization of law may be especially prominent in communities in which immigrants compose a larger and growing share (Johnson, Stewart, Pickett, & Gertz, 2011;Stewart, Martinez, Baumer, & Gertz, 2015;Stupi, Chiricos, & Gertz, 2016).…”
Section: Crime Reporting Levels May Be Enhanced In Immigrant Neighbormentioning
confidence: 99%
“…These studies, however, have not directly examined whites views of black criminality or, by extension, whether whites view blacks as posing a direct criminal threat to them. To address this research gap, we examine two dependent variables that accord with those used in prior studies that assess racial and ethnic threat processes (see, e.g., Barkan and Cohn , ; King and Wheelock ; Stults and Baumer ; Johnson et al ): Perceived black criminal threat and perceived black‐on‐white crime .…”
Section: Methodsmentioning
confidence: 99%